2019
DOI: 10.7759/cureus.4467
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Association of Osteogenesis Imperfecta with Bilateral Renal Osteodystrophy and Gastroenteritis in a Three-year-old Boy

Abstract: We describe a three-year-old male child who presented to the pediatrics out-patient department with a history of decrease in appetite, generalized weakness, on and off loose motions for one year, inability to walk and sit for eight months with a loss of neck holding for 14 days. On examination, the patient had a classic frog-shaped leg posture. X-rays of chest, skull, pelvis and long bones were performed which showed osteopenic bones, frontal bossing and multiple microfractures, which were classic for osteogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition, urinary excretion of calcium reportedly correlates with the clinical severity of the disorder, and hypercalciuria has been shown to be more frequent in patients with Sillence classification types II and III thanI ( 7 ). Most patients with OI with urolithiasis were classified as Sillence classification type III ( 4 , 5 , 7 ), supporting the notion that hypercalciuria is a contributing factor to urolithiasis. Given the above, we concluded that it is important to investigate the presence of hypercalciuria by 24-hour urine collection, and if hypercalciuria is found, attention should be paid to the complications of urolithiasis in patients with OI.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, urinary excretion of calcium reportedly correlates with the clinical severity of the disorder, and hypercalciuria has been shown to be more frequent in patients with Sillence classification types II and III thanI ( 7 ). Most patients with OI with urolithiasis were classified as Sillence classification type III ( 4 , 5 , 7 ), supporting the notion that hypercalciuria is a contributing factor to urolithiasis. Given the above, we concluded that it is important to investigate the presence of hypercalciuria by 24-hour urine collection, and if hypercalciuria is found, attention should be paid to the complications of urolithiasis in patients with OI.…”
Section: Discussionmentioning
confidence: 54%
“…One clinical matter is that OI can be complicated by urolithiasis. To our knowledge, only three cases, including ours, have been featured within case reports ( 4 , 5 ), but eight of 58 patients with OI (13%) were reported to have complications of urolithiasis, suggesting that it is not a very rare comorbidity ( 6 ). OI is known to present with hypercalciuria, which is a cause of urolithiasis (calcium-based kidney stones).…”
Section: Discussionmentioning
confidence: 71%
“… 28 Rachitic rosary may be observed in rickets and OI. 29 Fragile bones and fractures are frequently encountered in Menkes disease, vitamin D disorders, and OI; however, in OI, the predisposition to fracture is more common than in these other genetic disorders. 4 …”
Section: Questions/discussion Points Partmentioning
confidence: 99%